Happiness reconstruction through Islamic guidelines in blinds in The Muslim Blinds of Indonesia (ITMI) Central Java - Himawanti, Izza; Hidayatullah, Ahmad; Setiyono, Andhi (Journal of Advanced Guidance and Counseling, 2020)
Blind experience various psychological conditions that need attention, such as feeling inferior, hopeless, and useless so that it affects the level of happiness. The main purpose of this study is to determine the process of reconstruction of happiness in blind people through Islamic guidance. This research uses a qualitative method with a phenomenological approach; the process of data analysis uses the Interpretative Phenomenological Analysis technique. The subjects of the study were the blind who were members of ITMI (Indonesian Moslem Blind Association) and actively in Islamic guidance. The process of selecting subjects uses a purposive sampling method. The results showed that Islamic guidance had a positive influence in the process of reconstructing the happiness of the blind. Various processes of cognition and affection can be explored well during the process of Islamic guidance. The process of reconstructing happiness in the blind people goes through six stages, beginning with the stage of negative emotional conditions such as despair and anxiety, feeling isolated from the social environment, and then undertaking the process of finding meaning in life and reconstructing happiness.